퀼트기법을 활용한 원단 스와치 업사이클링 패션소품제작 연구 - 배석인; Bae Suk In; 강기용; Kang Ki Yong (기초조형학연구, 2019)
본 연구의 목적은 퀼트에서 표현할 수 있는 수공예적인 기법을 적용한 원단 스와치 업사이클 패션소품을 제작하여 폐소재의 업사이클링에 대한 가능성을 재조명하고, 업사이클링 패션소품의 디자인 방향을 제시하여 업사이클링 패션산업의 지속가능한 소재 발전에 도움이 되고자 한다. 이에 본 연구에서는 퀼트의 패치워크, 아플리케, 퀼팅의 업사이클 표현방법에 대해 연구하여 12가지의 기법으로 정리하고 원단 스와치를 소재로 사용하여 오방색과 가을 이미지의 업사이클 패션소품으로 스카프와 가방 총 24점을 제작하였다. 퀼트기법을 활용한 업사이클 패션소품제작 결과는 다음과 같다. 첫째, 패치워크 기법으로 조각을 연결하여 한 장의 원단으로 사용하거나 장식에 필요한 모티브로 사용하는 등 활용도가 매우 높은 디자인 소재를 제작할 수 있었다. 둘째, 특수 패치워크 기법으로 종류가 다른 원단을 구기거나 접어서 생기는 주름을 이용하여 표면 질감에 변화를 주어 비즈, 구슬 등으로 장식함으로써 다양한 입체적 표현을 가능하게 하였다. 셋째, 아플리케 기법으로 가장자리 연결에 사용하는 실의 색과 올 풀림 정도에 따라 다양한 변화를 줄 수 있었으며 스티치나 특수사를 사용하여 바느질의 형태를 드러나게 표현함으로써 질감의 변화와 장식성의 표현을 가능하게 하였다. 넷째, 퀼팅기법으로 연결된 조각의 시접선이나 패턴을 복합사나 메탈사, 레이온사, 자수사 등의 실을 사용하여 밀도감과 공간감의 변화를 통해 표면에 다양한 질감의 표현을 가능하게 하였다. 이를 통하여 제작된 소품은 다양한 수공예적인 감성을 나타내기 적합하였으며 수공예적인 가치와 희소성을 부각시켜 업사이클 제품의 상품화 가능성을 제시하고자 하였다. 앞으로도 후속 연구를 통하여 업사이클링 소재를 활용한 패션디자인 분야에서 새로운 가치를 창출하는데 도움이 되기를 기대해 본다. The purpose of this study is to review the possibilities of upcycling of waste materials by making fabric swatch upcycle fashion accessories using hand crafted techniques that can be expressed in quilts, and to suggest the design direction of up to contribute to the development of sustainable materials. In this study, we studied the method of expressing upcycle of patchwork, applique and quilting of quilts and compiled them into 12 techniques. And Using fabric swatches as materials, up-cycle fashion accessories(scarves, bags) of the five colors and autumn images were produced. The results of up-cycle fashion accessories using quilting technique are as follows. First, we could create a very useful design material by connecting the pieces with a patchwork technique and using them as one piece of fabric or as a motif needed for decorating. Secondly, by using a special patchwork technique, the surface texture is changed by using wrinkles generated by folding or folding fabrics of different kinds, so that various stereoscopic expressions are possible by decorating with beads and beads. Third, we could make a variety of changes according to the color of yarn used for edge connection and the degree of loosening. And by using stitch or special yarn to express the shape of stitching, it is possible to express the change of texture and ornamentality. Fourth, by using quilting technique, it is possible to express various textures on the surface through the change of density and space by using threads such as composite yarn, metal yarn, rayon yarn, and embroidery yarn. The small items produced by this study were suitable to show various handicap sensibilities. And to propose the possibility of commercialization of upcycle products by highlighting handicraft value and scarcity. I hope that future research will help to create new value in the field of fashion design using up-cycling materials.